Lingual thyroid: diagnosis using a hybrid of single photon emission computed tomography and standard computed tomography - Dolezal, J; Vizda, J; Horacek, J; Spitalnikova, S (Journal of laryngology & otology, 2013)
AIM: To present a rare case of lingual thyroid detected using a hybrid of single photon emission computed tomography and standard computed tomography in a young woman with hypothyroidism. MATERIALS AND METHODS: A 29-year-old woman was screened for autoimmune thyroid disorders in early pregnancy, and found to have subclinical hypothyroidism. No thyroid tissue was found in the anterior neck upon ultrasonography, raising suspicions of an ectopic thyroid. The patient was treated with levothyroxine throughout the remainder of her pregnancy, and developed postpartum thyroiditis requiring an increase in levothyroxine dosage. Whole-body scintigraphy and zoomed static head and neck scintigraphy were performed. Abnormal 99mTc-pertechnetate uptake was observed in the oral region, whereas no uptake was found in the usual thyroid location. Hybrid imaging using single photon emission computed tomography and standard computed tomography was performed to improve three-dimensional representation of the area of increased activity. RESULTS: The latter imaging modality detected ectopic thyroid tissue in the tongue. CONCLUSION: Whole body 99mTc-pertechnetate scintigraphy and a hybrid of single photon emission computed tomography and standard computed tomography are effective imaging modalities for the investigation of ectopic thyroid tissue. The latter modality is particularly recommended, as it allows more precise spatial visualisation of increased isotope uptake activity in the head and neck.
Keywords: počítačová rentgenová tomografie; jednofotonová emisní výpočetní tomografie; Lingual Thyroid; Pregnancy; Humans; lidé středního věku; lingvální ektopie štítné žlázy; Female; Aged; mladý dospělý; dospělí; Thyroid Dysgenesis; Thyroid Gland; Hypothyroidism; tomografie emisní počítačová; dysgeneze štítné žlázy; senioři; lidé; Tomography, Emission-Computed; štítná žláza; Adult; hypotyreóza; ženské pohlaví; Male; Middle Aged; Tomography, X-Ray Computed; těhotenství; Young Adult; mužské pohlaví; Tomography, Emission-Computed, Single-Photon